MATERNAL AND CHILD CARE IN THE POSTPARTUM - Carolina Salustino dos Santos, Maria; Corrêa Bezerra de Araújo, Renata; Alexandre Judeikis, Guilherme; Teixeira Regis, Claudio; Paula Carvalho Ramos, Ana; Claudino do Nascimento, Nathalia; Feitosa Rodrigues, Lutigard; Araújo de Oliveira, Carolyna (Health and Society, 2022)
The postpartum/puerperium is a moment experienced by the mother and her baby, in which there is a need for family and professional support. This study is reflective, written in the year 2022, through shared readings. It is understood that the postpartum period should be seen in an integral way, aiming at the well-being of the binomial, so professional guidance and due care are essential for the comfort of those involved.